Jordan : Third Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the Third Review Under the Stand-By Arrangement on Jordan highlights the economic developments and policies. Additional grants and higher tax revenue will offset the loss of the oil surplus and the increase in petroleum subsidies. The authorities intend to limit total budgetary expenditure to the program level with a view to achieving the fiscal deficit target. The authorities recognized an upside potential on the revenue side, and in such an event, they intend to save a large portion of the overperformance for further deficit and debt reduction.